Phosphate‐binding protein from Polaromonas JS666: purification, characterization, crystallization and sulfur SAD phasing. Issue 6 (1st June 2017) - Pegos, Vanessa R.; Hey, Louis; LaMirande, Jacob; Pfeffer, Rachel; Lipsh, Rosalie; Amitay, Moshe; Gonzalez, Daniel; Elias, Mikael
Abstract : A phosphate‐binding protein from Polaromonas JS666 has been isolated, purified, characterized and crystallized. As it shares only 31% sequence identity with its closest known homologous structure, molecular‐replacement approaches failed and the structure was solved using the sulfur SAD method. Its structure is expected to reveal its binding cleft and explain its maximal phosphate‐binding activity at basic pH. Abstract : Phosphate‐binding proteins (PBPs) are key proteins that belong to the bacterial ABC‐type phosphate transporters. PBPs are periplasmic (or membrane‐anchored) proteins that capture phosphate anions from the environment and release them to the transmembrane transporter. Recent work has suggested that PBPs have evolved for high affinity as well as high selectivity. In particular, a short, unique hydrogen bond between the phosphate anion and an aspartate residue has been shown to be critical for selectivity, yet is not strictly conserved in PBPs. Here, the PBP from Polaromonas JS666 is focused on. Interestingly, this PBP is predicted to harbor different phosphate‐binding residues to currently known PBPs. Here, it is shown that the PBP from Polaromonas JS666 is capable of binding phosphate, with a maximal binding activity at pH 8. Its structure is expected to reveal its binding‐cleft configuration as well as its phosphate‐binding mode. Here, the expression, purification, characterization, crystallization and X‐ray diffraction data collection to 1.35 Å resolution of the PBP from Polaromonas JS666 are reported.